Evaluation of Oil Palm Empty Fruit Bunch Compost Application on Samhong Mustard (Brassica juncea L.) Cultivation in Polybags - Kumara, Nur Rizha Adi; Sumiahadi, Ade (Applied Research in Science and Technology, 2024)
Background: Samhong is a mustard variety that is becoming increasingly popular in Indonesia. To increase its production, appropriate cultivation technologies are necessary, such as enriching the growing medium with organic matter. One organic material that can be utilized is compost made from oil palm empty fruit bunches (OPEFB). OPEFB is the solid waste remaining after oil has been extracted from the flesh (mesocarp) and kernel (endocarp) of fresh oil palm fruits.Aims & Methods: This study aimed to evaluate the effects of different OPEFB compost dosages on the growth and yield of samhong mustard plants. The research was conducted from March to May 2023 at the Experimental Field of the Faculty of Agriculture, Universitas Muhammadiyah Jakarta. The study utilized a Randomized Complete Block Design (RCBD) with five treatment levels, consisting of a control group using inorganic NPK fertilizer and four different doses of OPEFB compost (25, 50, 75, and 100 g/plant).Result: The results of this study indicate that, in general, all OPEFB compost applications resulted in lower growth and yield compared to the NPK control. However, a positive trend was observed where higher compost doses led to improved plant growth. Furthermore, correlation analysis revealed a strong to very strong positive correlation between OPEFB compost dose and the growth of above-ground parts and yield of the plants. This study indicated that OPEFB compost has potential to be used as organic fertilizer with higher doses.